Salvianolic acid A attenuates CCl4-induced liver fibrosis by regulating the PI3K/AKT/mTOR, Bcl-2/Bax and caspase-3/cleaved caspase-3 signaling pathways - Wang R; Song F; Li S; Wu B; Gu Y; Yuan Y (Dove Medical Press, 2019)
Rong Wang*, Fuxing Song*, Shengnan Li, Bin Wu, Yanqiu Gu, Yongfang YuanDepartment of Pharmacy, Shanghai 9th People‘s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 201999, People’s Republic of China*These authors contributed equally to this work Background: Liver fibrosis occurs due to chronic liver disease due to multiple pathophysiological causes. The main causes for this condition are chronic alcohol abuse, nonalcoholic steatohepatitis, and infection due to hepatitis C virus. Currently, there is more and more information available about the molecular as well as cellular mechanisms, which play a role in the advancement of liver fibrosis. However, there is still no effective therapy against it.Purpose: In order to find an effective treatment against liver fibrosis, our study explored whether salvianolic acid A (SA-A), a traditional Chinese medicine extracted from the plant Danshen, could effectively inhibit the liver fibrosis, which is induced by CCl4 in vivo.Methods: The effects of SA-A were evaluated by assessing the parameters related to liver fibrosis such as body weight, histological changes, and biochemical parameters. Thereafter, the related protein or gene levels of P13K/AKT/mTOR, Bcl-2/Bax and caspase-3/cleaved caspase-3 signaling pathways were determined by western blotting, real-time PCR or immunohistochemistry staining.Results: According to the results of our study, SA-A could reduce liver fibrosis by inhibiting liver function, liver fibrosis index, collagen deposition, and improving the degree of liver fibrosis in rats. Mechanistically, the PI3K/AKT/mTOR signaling cascade was inhibited by SA-A to prevent the stimulation of hepatic stellate cell, as well as the synthesis of extracellular matrix, and regulated Bcl-2/Bax and caspase-3/cleaved caspase-3 signaling pathways to prevent hepatocyte apoptosis.Conclusion: The novel findings of this study suggested that SA-A could reduce liver fibrosis and the molecular mechanisms behind it are closely associated with the regulation of PI3K/AKT/mTOR, Bcl-2/Bax and caspase-3/cleaved caspase-3 signaling pathways.Keywords: liver fibrosis, salvianolic acid A, AKT/mTOR, Bcl-2/Bax, caspase-3/cleaved caspase-3